New records of deep-sea shrimps of family Solenoceridae Wood-Mason & Alcock, 1891 (Crustacea: Decapoda: Dendrobranchiata) from Southwestern Atlantic - Alves-Júnior, Flavio De Almeida; Araújo, Marina De Sá Leitão Câmara De; Souza-Filho, Jesser F. (Zootaxa, 2017)
This paper reports the occurrence of four deep waters shrimps of the family Solenoceridae in the southwestern Atlantic, Brazil. The rare Hadropenaeus modestus is collected for the second time from Brazilian waters after 138 years, filling the gaps on its distributional pattern. Mesopenaeus tropicalis is a new register for Potiguar basin, although it is common along Brazilian coast. Hymenopenaeus chacei and H. laevis are recorded for the first time in southwestern Atlantic. The records of these species in the southwestern Atlantic are an important advancement to raise the knowledge of the deep-sea shrimps.